Coal-fired power plants and industrial development - Leonard Missbach; Jan Christoph Steckel; Sebastian Renner; Sebastian Kraus (ZBW - Leibniz Information Centre for Economics, 2024)
Past periods of industrial development have gone hand in hand with the burning of coal, but there is little evidence on the effects of coal infrastructure on manufacturing growth in today's industrializing economies. We quantify the direct and indirect effects of coal-fired power plant commissioning on local incumbent manufacturing firms in Indonesia during a coal phase-in period between 1984 and 2015. We analyze spatially and temporally explicit manufacturing and power plant data in a stacked difference-in-difference framework. Leveraging quasi-random variation in treatment timing, we show that coal-fired power plants have led incumbent larger firms to increase employment, inputs, and outputs. In contrast, smaller firms remained unaffected. We identify mediating channels including improved electricity supply and transportation infrastructure, and increased competition for labor. Ongoing efforts to reduce global coal capacity need to take such effects into account.
Keywords: C55; L60; O12; O14; O53; Q40; R11; 330; Coal; Manufacturing; Industrialization; Indonesia; Difference-in-difference